Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes - Orel Šanko , Nena (University of Maribor Press, 2026)
The university textbook "Interdisciplinary and Applied Knowledge for Green and Digital Logistics Processes" is a comprehensive guide aimed at supporting sustainable and digital approaches in logistics. It focuses on reducing the environmental impact of logistics processes and improving their efficiency through the use of various supporting mechanisms. The interdisciplinary approach combines knowledge from multiple fields, enabling a holistic understanding of modern logistics and the application of practical knowledge to areas beyond logistics. Readers are equipped with practical skills and expertise to enhance the efficiency and sustainability of individual processes. The textbook covers topics such as leadership and communication, data-driven business decision-making, information and computer literacy, the importance of promotional video content, the organization of sustainable travel, sustainable mobility, and the logistics of a dispersed hotel. The entire content is aimed at strengthening the competencies that are essential for successfully managing modern logistics challenges.